Use of colour etching in the structural analysis of graphitic cast irons - Vasko, Alan; Belan, Juraj; Tillova, Eva (Manufacturing Technology Journal, 2020)
Colour metallography, especially colour etching, is a widely used technique for visualizing different phases in the structure of metals. Its advantage to the traditional etching techniques is that it gives additional information about the structure of material. The paper deals with the structural analysis of graphitic cast irons with a focus on colour etching. The possibilities of extending information about the structure of cast irons using colour contrast compared to classic black-and-white contrast is discussed. The paper is supplemented by photographs of microstructures of graphitic cast irons, obtained using classic black-and-white methods, as well as colour etching. Colour photographs of the structure of cast irons were obtained using the light metallographic microscope Neophot 32 with a digital camera Nikon DS-Fi3. Selected etchants for traditional black-and-white etching and for colour etching were used.
Keywords: Structural analysis; Colour metallography; Colour etching; Etchant; Graphitic cast iron